Dissociation and recovery in psychosis – an overview of the literature - Calciu, Claudia; Macpherson, Rob; Chen, Sui Yung; Zlate, Madalina; King, Rosemary C.; Rees, Kerry J.; Soponaru, Camelia; Webb, Jackie (Frontiers in Psychiatry, 2024)
The relationship between dissociation and recovery from psychosis is a new topic, which could attract the interest of the researchers in the field of dissociation due to its relevance to their daily clinical practice. This review brings together a diversity of international research and theoretical views on the phenomenology of dissociation, psychosis and recovery and provides a synthesis by narrative and tabulation of the existing knowledge related to these concepts.The objective was to make a synthesis by narrative and tabulation about what is known on the topic.The systematic search was conducted according to the PRISMA-statement in the databases Medline, PsycInfo, PubMed and Google Scholar. 2110 articles were selected according to the inclusion and exclusion criteria detailed in the methods, and 19 records were included in the review.Outcomes None of the included publications put together, in the same conceptualisation or hypothesis, dissociation and the recovery from an episode of psychosis, therefore this matter remains unstudied at this time.The process of reviewing the existing scientific literature in the field of dissociation and recovery from psychosis has been very useful for charting the direction that future research will take.